Gingivectomy in Altered Passive Eruption US an Aesthetic Gingival Correction Approach: A Case Report - Andriani, Ika; Rahmadhani, Nureza; Azzahra, Davina Anindya (Universitas Baiturrahmah, 2025)
Introduction: Altered passive eruption (APE) is a mucogingival condition with the margin being positioned too far coronally, thereby covering a portion of the anatomical crown. This condition often leads to aesthetic concerns, specifically an excessive gingival display known as a gummy smile. This case report aims to demonstrate the effectiveness of gingivectomy as a single surgical procedure in aesthetic correction in cases of APE. Case and Management: A 23-year-old female patient presented with a chief complaint of short and small maxillary anterior teeth. Clinical examination revealed symmetrical gingiva with a rubbery consistency and slight bleeding on probing. Clinical crown length measurements showed a shorter-than-normal size. Periapical radiographs confirmed that the distance between the cemento-enamel junction (CEJ) and the alveolar crest was within normal limits, justifying a soft-tissue-only approach. After an initial phase of periodontal therapy to control inflammation, gingivectomy was performed using an external bevel incision technique. The procedure was followed by gingivoplasty to reshape the gingival contour for a more proportional outcome. Post-operative evaluation showed a significant increase in clinical crown length, improved plaque index, and a more harmonious gingival contour. The patient expressed high satisfaction with both the aesthetic and functional results. Conclusion: Gingivectomy is an effective and minimally invasive surgical option for correcting aesthetic issues resulting from altered passive eruption The success of this case underscores the importance of a correct diagnosis and a clear understanding of the etiology before determining a treatment plan.